CONGENITAL rNTERNAL HYDROCEPHALUS IN A NEW BORN COW CALF - JANA, DEBASIS; GHOSH, MOUSUMI (The Indian Journal of Animal Reproduction, 2023)
A case of congenital internal hydrocephalus in a new born indigenous cow calf and its successful therapeutic management has been reported.